(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2026)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: Euro+Med Plant Base (2025), Hassler (1994–2025), POWO (2025). Results: According to the APG IV classification, the families Elaeagnaceae, Rhamnaceae, Cannabaceae (incl. Celtidaceae), Moraceae, Ulmaceae and Urticaceae are included in the order Rosales, however in this article they are still treated as belonging to two orders: Rhamnales (Elaeagnaceae, Rhamnaceae) and Urticales (Cannabaceae (incl. Celtidaceae), Moraceae, Ulmaceae, Urticaceae). In the flora of Ukraine, the family Elaeagnaceae includes three genera (Elaeagnus Tourn. ex L., Hippophae L., Shepherdia Nutt.) and 8 species, of which only one species is autochthonous (Hippophae rhamnoides L.), while all others are cultivated and escape from cultivation. The family Rhamnaceae is rep-resented by five genera and 12 species, of which three genera and four species are indigenous (Frangula alnus Mill., Paliurus spina-christi Mill., Rhamnus cathartica L., R. saxatilis Jacq. subsp. tinctoria Nyman). The Cannabaceae family includes three genera (Cannabis L., Celtis L., Humulus L.) and 8 species, half of which are cultivated and escape from cultivation. Cultivated hemp (Cannabis sativa L.) and wild hemp (C. ruderalis Janisch.), which are treated as a single taxon, are here considered as two closely related species that differ in fruit morphology and perianth structure, as well as biological features. In Ukraine, the Moraceae family is represented by four genera and five cultivated species. The Ulmaceae family includes two genera – the native Ulmus L. and the cultivated Zelkova Spach. Previously, the genus Celtis L., which is now included in the family Cannabaceae, was also placed in the Ulmaceae in domestic floristic treatments. Synonyms of Ulmus glabra Huds. include U. campestris, U. elliptica, U. scabra; synonym of U. laevis Pall. includes U. celtidea; synonyms of U. minor Mill. include U. carpinifolia, U. corylifolia, U. foliacea, U. suberosa, U. wyssotzky, which were previously listed for Ukraine as separate species. The Urticaceae family includes two genera: Parietaria L. (three species), Urtica L. (seven species). A synonym of U. pubescens Ledeb. is the name U. galeopsifolia under which the species was previously listed for Ukraine.